2019
DOI: 10.1590/fst.38417
|View full text |Cite
|
Sign up to set email alerts
|

Different formulations of camu-camu popsicle: characterization, vitamin C and sensorial analysis of an opportunity to family agroindustry

Abstract: The high levels of vitamin C in camu-camu have stimulated the interests of extractivists, farmers and consumers. The aim of this study was to characterize five accessible for family agroindustry different formulations of camu-camu popsicles and assess their acceptance. A completely randomized design was used and the treatments consisted of five different popsicle formulations: camu-camu pulp (T1 and T2: 27%, T3 and T4: 20.8%; T5: 61%), water (T1 and T2: 43.5%, T3 and T4: 20.8%; T5: no water), whole milk powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
2
9
1
1
Order By: Relevance
“…The average acidity values of the jellies tested in the present study are still higher than those reported in the literature (Grigio et al, 2019(Grigio et al, , 2021Oliveira et al, 2014a, b;Santos et al, 2012;Viana et al, 2015). The average values observed in the present study are higher than those reported for rose apple (Syzygium jambos) jelly (Cardoso, 2008), probably due to the high acidity present in camu-camu.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…The average acidity values of the jellies tested in the present study are still higher than those reported in the literature (Grigio et al, 2019(Grigio et al, , 2021Oliveira et al, 2014a, b;Santos et al, 2012;Viana et al, 2015). The average values observed in the present study are higher than those reported for rose apple (Syzygium jambos) jelly (Cardoso, 2008), probably due to the high acidity present in camu-camu.…”
Section: Discussioncontrasting
confidence: 67%
“…This fact is evidenced by observing the correlation analysis, which shows a high negative correlation between the acceptability of the product with the levels of phenolic and antioxidant compounds. Similarly, when the pure pulp was used, there was a greater rejection of camu camu popsicle (Grigio et al, 2019(Grigio et al, , 2021. Therefore, there is a clear need to find fruit formulations that allow the maximum nutraceutical potential to be exploited and that obtain excellent consumer acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect that influenced the coloring of the popsicles due to the mixtures of the ingredients, in which the appearance, color, flavor, and texture indices were responsible for the highest acceptability index. Similarly reported by Grigio et al (2019) in which the use F I G U R E 3 Principal component analysis (PC) performed in different popsicle formulations and intention to buy products, sensory characteristics, organoleptic quality and bioactive compounds (n = 114). The red circle symbol corresponds to formulation 1: without milk; o brown triangle symbol formulation 2: without milk + lyophilized peel; the green square symbol a formulation 3: with milk; the blue plus (+) symbol a formulation 4: with milk + lyophilized peel; the blue open square symbol a formulation 5: with milk + chocolate coating; and the plus symbol (+) pink a formulation 6: with milk + lyophilized peel + chocolate coating) of color is decisive for a better acceptance of popsicles based on camu-camu.…”
Section: Discussionmentioning
confidence: 99%
“…This food is a complex aerated emulsion containing milk proteins and fats that have an important role in stabilizing its structure. This matrix is formed by a frozen phase containing air bubbles, fat particles, and ice crystals (Balthazar et al, 2017;Ayed et al, 2018;Grigio et al, 2019). According to Góral et al (2018), the primary ingredient in ice cream is cow's milk, which contains several beneficial substances for the human body, such as protein, fat, lactose, vitamins, and mineral compounds.…”
Section: Introductionmentioning
confidence: 99%